Main currents of Marxism: is origins, growth and dissolution - Kolakowski, Leszek (Washington, 1978)
In this first volume, Leszek Kolakowski examines the origins of Marxism, tracing its descent, through Hegel and the Enlightenment, from the neo Platonists. He analyses the development of Marx's thought and shows its divergence from other forms of socialism.
Keywords: Communism history